Fouling resistance and cleaning efficiency of stimuli-responsive reverse osmosis (RO) membranes. (26th October 2016) - You, Meng; Wang, Pan; Xu, Mingli; Yuan, Tao; Meng, Jianqiang
Abstract: A series of stimuli-responsive reverse (RO) membranes were prepared by tethering three stimuli-responsive polymers, poly (sulfobetaine methacrylate) (PSBMA), poly (4-(2-Sulfoethyl)-1-(4-vinyl-benzyl) pyridinium betain) (PSVBP) and poly (N-isopropylacrylamide) (PNIPAM) onto the surface of a commercial thin-film (TFC) RO membrane via surface-initiated graft polymerization. The membrane surface was characterized by ATR-FTIR, XPS, zeta potential, water contact angle (WCA), FESEM and AFM. Membrane characterization indicates successful grafting of these polymers, with more negatively-charged, smoother and more hydrophilic surfaces as a result. Long-term fouling-rinsing cycled experiments were conducted to evaluate fouling resistance and cleaning efficiency. With CaCO3 as the foulant, the modified membranes showed better fouling resistance in the whole testing as long as 320 h; with BSA as the foulant, they only showed better antifouling performance in short term. However, the modified membranes showed much higher cleaning efficiency in both cases, with the PA-g-PSVBP membrane as the best one. Graphical abstract: Highlights: Three stimuli-responsive polymers were grafted onto a TFC RO membrane. The grafting produces negatively-charged, smoother and hydrophilic surfaces. The membranes show much better fouling resistance to scaling. The membranes only show better resistance to BSA fouling in short term. The modified membranes showed much higher cleaning efficiency.